Pemberdayaan UMKM Kabupaten Simalungun Melalui Penyuluhan Strategi Pemasaran, Digital Marketing dan Penyusunan Laporan Keuangan - Sihite, Mislan; Saragih, Henri; Mesakh, Januardi; Ijonris, Yusuf; Gultom, Robinhot; Sianturi, Jeudi A. T. P.; Sinurat, Elperida J.; Sipayung, Tri Darma; Melianna, Saur; Sembiring, Rasmulia; Rajagukguk, Tiur; Marbun, Sondang Ni Bulan; Panggabean, Toman; Nadapdap, Kristanty M. N.; Purba, Jon Henri (Jurnal Pengabdian Pada Masyarakat METHABDI, 2024)
Simalungun Regency is one of the regencies in North Sumatra Province, Indonesia. This district is home to the Simalungun Batak people. The Community Service Team (PKM) provides enlightenment to the community and MSME actors in Simalungun Regency in order to increase their income. In general, mothers in the neighborhood live at home and therefore the PKM Team provides a way to increase their income. The aim of PKM is their knowledge and insight in managing a business. Apart from that, this PKM activity is to train the community and MSME players in running their businesses and this activity provides tips and strategies for managing a business, marketing strategies in doing business, preparing simple business bookkeeping, and the role of digital marketing in a business. This activity equips people in entrepreneurship and motivates them to become entrepreneurs. PKM participants are expected to have creative ideas and be able to run their businesses better, in terms of management, marketing and business capacity, which will ultimately increase income.